INTRODUKSI PEMBUATAN ASINAN UNTUK MEMPERPANJANG MASA SIMPAN BUAH SALAK DI DESA SIBETAN KARANGASEM - A. S., Duniaji; Mahatma, I. A; Wisaniyasa, Ni. W; Puspawati, N. N. (Buletin Udayana Mengabdi; Vol 13 No 2 (2014): Vol 13, No. 2 (2014), 2014)
There are many varieties of salak. Salak Pondoh, Salak Manonjaya and one of very popular is Salak Bali. The taste of Salak Bali is usually sweet and acidic taste, but its pineapple-, pear-, and banana-like aroma, texture very dry and crumbly. Good Manufacturing Practices (GMP) with specific Standard Operating Procedures (SOP) has been recognized as the requirement of quality and safety management system, competition tools in the global market to improve growers’ knowledge and skills on producing commodities in managing farms and products. The community service was done on July- August 2014 to the women farmer group of KWT Srada and KWT Subak Abian Salak at village Sibetan, Bebandem Distric of Karangasem. The objective of training was to improve the skill of women farmer group on snake fruit pickles products. A number of eight kinds of snake fruits pickle product has been produced. The training has been improving the skill of women farmer group of KWT Srada and KWT Subak Abian Salak at Sibetan to produce the good quality snake fruit pickles products in global market competition. Key word: salak, snake fruit pickles